(untitled) (Research, Society and Development, 2022)
Given the need to reduce production costs and make pesticide-free products available in the watermelon supply chain, the objective of this study was to evaluate the influence of bacteria of the genus Bacillus subtilis and Bacillus megaterium on germination and biometry of watermelon seeds and seedlings. cv. Sugar Baby. The research was carried out at the Centro de Ciências de Chapadinha, of the Universidade Federal do Maranhão (CCCh/UFMA). The study was carried out in a completely randomized experimental design in a 5x3 factorial scheme (five immersion times (0, 6, 12, 18 and 24 hours) x three bioinputs (B. subtilis; B. megaterium and the co-inoculation of B. subtilis + B. megaterium)) with 40 replications. Data were submitted to ANOVA and means were compared by the Duncan test (P<0.05). The results show that the co-inoculation of Bacillus subtilis and Bacillus megaterium is recommended to potentiate the action of microorganisms on seed germination and biometry of watermelon cv. Sugar Baby, being that the immersion time of 6 hours provides greater increment in the biometric variables and the time of 12 and 0 hours presents better germination performance.